E-Service Quality Factors and Customer Satisfaction in Shopee’s E-Commerce Platform - Mardhotillah, Rachma Rizqina; Wibawa, Berto Mulia (Universitas Dinamika, 2025)
The rapid growth of e-commerce has intensified competition among platforms in providing the best services to customers. Shopee, one of the largest e-commerce platforms in Southeast Asia, faces challenges in maintaining e-service quality that enhances customer satisfaction. This study aims to analyze the influence of security, reliability, and responsiveness on e-service quality, as well as its impact on customer satisfaction in Shopee's e-commerce platform. This research employs a quantitative approach with purposive random sampling, involving 150 Shopee users as respondents. The data collected were analyzed using structural equation modeling-partial least squares (SEM-PLS). The results indicate that security, reliability, and responsiveness have a positive and significant impact on e-service quality. Furthermore, e-service quality positively and significantly influences customer satisfaction. These findings suggest that transaction security, system reliability, and customer service responsiveness are key factors in building high-quality e-commerce services. Therefore, Shopee must continuously improve its security system, maintain platform stability, and enhance customer service responsiveness to increase customer satisfaction and loyalty.